ANALISIS PENGARUH BRAND EQUITY TERHADAP KEPUTUSAN PEMBELIAN AIR MINUM DALAM KEMASAN AQUA â DANONE (Studi Kasus Konsumen Kecamatan Kota Rembang) (STIE YPPI Rembang, 2014)
AbstractThe development of information technology and provide changes to the mindset of the people associated with fulfillment. People are starting to switch to the products and goods and services that have a good credible, either prestice and quality. One of them choose a product that has a good brand equity. In the brand, there is a commitment to service and commitment to quality products and services provided by the seller. Brand equity has an important role in the customer purchase decision. Brand equity will facilitate consumers in making purchasing decisions both tangible products and services they consume. Globally, any brand or brands on the product will form the image of the goods and services in the minds of consumers. Therefore, companies are required to manage and develop its brand equity in order to survive in a competitive business.Â Key Word : Brand Equity, Buying Decision.Â